Clinical Evaluation of Tavocept to Decrease Diuresis Time and Volume in Dogs with Bladder Cancer Receiving Cisplatin. (27th October 2017) - Henry, C.J.; Flesner, B.K.; Bechtel, S.A.; Bryan, J.N.; Tate, D.J.; Selting, K.A.; Lattimer, J.C.; Bryan, M.E.; Grubb, L.; Hausheer, F.
Abstract : Background: Transitional cell carcinoma is the most common bladder cancer of dogs. Cisplatin combined with piroxicam provides superior response rates, but unacceptable rates of nephrotoxicity. Tavocept is a chemoprotectant that has mitigated cisplatin toxicity and decreased the required infusion/diuresis volume in clinical trials in humans. Hypothesis/Objectives: We hypothesized that Tavocept would decrease diuresis volume and time and facilitate safe administration of a cisplatin/piroxicam protocol to dogs with bladder cancer. Secondary objectives were to compare response rate and survival times to an historical comparator group treated without Tavocept. Animals: Fourteen client‐owned dogs were prospectively enrolled. Methods: Tumor volume was measured by computed tomography at days 0, 42, and 84. Dogs received combination Tavocept/cisplatin with a shortened diuresis protocol. A total of 4 doses was planned, with concurrent administration of piroxicam. Serial biochemical analyses were evaluated for azotemia. Results: A 90‐minute infusion/diuresis time was used for all dogs. Three dogs (21%) had concurrent increases in serum creatinine (>2.0 mg/dL) and BUN (>42 mg/dL) concentrations; 2 of these dogs were isosthenuric. This frequency of nephrotoxicity is significantly less ( P = 0.0406) than that of an historical control group treated without Tavocept. Overall response rate was 27%. Median survival time was comparable to historical controls (253 vs. 246 days). Conclusions and Clinical Importance: Tavocept decreased the required diuresis time with cisplatin from > 6 hours to 90 minutes, while also decreasing occurrence of azotemia. Survival time was comparable, but the response rate was inferior to an historical comparator group. Further evaluation in other tumors susceptible to platinum agents is warranted.